2016
DOI: 10.1016/j.nmni.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of multidrug-resistant Acinetobacter baumannii producing OXA-23 Carbapenemase in Qatar

Abstract: The objective of our study was to describe the molecular support of carbapenem resistance from randomly selected clinical isolates of multidrug-resistant (MDR) Acinetobacter baumannii as a pilot study from the Hamad Medical Corporation (HMC), Qatar. Results of our report will be used to study carbapenemases using molecular techniques in all isolated MDR A. baumannii. Forty-eight MDR A. baumannii were randomly selected from isolates preserved at HMC. Identification of all isolates was confirmed by matrix-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
4
28
0
Order By: Relevance
“…The percentage of bla OXA-23 -like gene detected in impenem resistant isolates were 69.7% (23/33), this result is in agreement with Zowawi et al, 2015;Luo et al, 2015, different percentages of presence of bla OXA-et al, 2013), 100% by Fouad et al 2013, and others also reported all over the world as those reported by Cherkaoue et al, 2015(51.8%), Val et al, 2015(85%), 85.7% ElAbd et al, 2014and 100% Rolain et al, 2016 None of the impenem resistant isolates were positive for bla OXA-24 -like or bla OXA-58 -like genes this result was in agreement with Rolain et al, (2016). However bla OXA-58 -like, and bla OXA-24/40 -like genes were detected in lower rate than ofbla OXA-23 -like genes in many studies in Egypt as that by Al Agamy et al, (2014)who reported that A. baumannii carryingbla OXA-58 -like gene were 5% and that carrying bla OXA-24/40 -like gene is 7.5% ,and another study by AlHassan et al(2013) reported that the percentage of bla , and bla OXA-58 were 2.9%, and 14.7%, respectively.…”
Section: Resultssupporting
confidence: 77%
“…The percentage of bla OXA-23 -like gene detected in impenem resistant isolates were 69.7% (23/33), this result is in agreement with Zowawi et al, 2015;Luo et al, 2015, different percentages of presence of bla OXA-et al, 2013), 100% by Fouad et al 2013, and others also reported all over the world as those reported by Cherkaoue et al, 2015(51.8%), Val et al, 2015(85%), 85.7% ElAbd et al, 2014and 100% Rolain et al, 2016 None of the impenem resistant isolates were positive for bla OXA-24 -like or bla OXA-58 -like genes this result was in agreement with Rolain et al, (2016). However bla OXA-58 -like, and bla OXA-24/40 -like genes were detected in lower rate than ofbla OXA-23 -like genes in many studies in Egypt as that by Al Agamy et al, (2014)who reported that A. baumannii carryingbla OXA-58 -like gene were 5% and that carrying bla OXA-24/40 -like gene is 7.5% ,and another study by AlHassan et al(2013) reported that the percentage of bla , and bla OXA-58 were 2.9%, and 14.7%, respectively.…”
Section: Resultssupporting
confidence: 77%
“…Also, our results were nearly confirmed by Gao et al [28] who confirmed that (100%) of the carbapenem resistant isolates showed positive results for the presence of OXA 51 gene, (94%) for OXA 23, and the other two resistance genes (OXA 24 and OXA 58) were not detected in any of the strains. Same results were revealed by Rolain et al [29] in Hamad hospital in Qatar, that conveyed that (100%) of A. baumannii isolates were positive for OXA-23; none were positive for OXA-24, OXA-58 [30].…”
Section: Discussionsupporting
confidence: 68%
“…Those studies showed that during the study period, ESBL prevalence ranged between 9% to 31.7% based on the data with clinical isolates ( n = 2166) [ 44 , 46 , 47 ]. Molecular characterization with the use of PCR demonstrated that bla OXA and bla CTX-M were the most prevalent ESBL traits among E. coli and ESKAPE pathogens, a smaller number of clinical isolates were reported to express bla TEM and, bla SHV ESBL traits ( Table 2 ) [ 44 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%